An Evaluation of Halal Tourism Program in East Lombok Regency Using Kirkpatrick’s Model - Fithry, Syawalina; Anwar, Syafri (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research was aimed to describe an evaluation of Halal Tourism program in East Lombok Regency, Nusa Tenggara Barat Province, Indonesia. This study was a program evaluation research which employed Kirkpatrick’s evaluation model (Reaction, Learning, Behavior, Result) and descriptive qualitative approach. Instruments of data collection were interview guideline, observation guideline, document review, and questionnaire. The data was analysis by using Miles and Huberman’s model which consisted of data display, data reduction, and conclusion drawing/verification. The result of this research showed that the reaction of Government Tourism Office and local community in East Lombok Regency towards Halal Tourism program was at moderate category (75.46%); community’s reaction towards the learning and carrying capacity of Halal tourism program was at moderate category (75.17 %); community’s knowledge of Halal Tourism scored 82.93 %; management system, both operational and administrative, scored 70.62 %; and Community’s reaction towards the aspects of Halal Tourism program scored 79.03%. The effectiveness of Halal Tourism program according to community’s reaction towards facility aspects scored 65.52 or was at moderate category. Moreover, the result from questionnaire revealed that 91.67% of participants thought that the knowledge they obtained in Halal Tourism program was less practical.